Des réseaux de référence au service de l’élevage durable de demain - LUCBERT, J.; DOCKÈS, A.C.; GERVREAU, G.; MADELINE, Y.; SEEGERS, J.; BAUMONT, R.; PEYRAUD, J.L. (INRAE Productions Animales, 2015)
Nouvelles de la Recherche : Des réseaux de référence au service de l’élevage durable de demain